On the South China Sea numerical model - Camerlengo, Alejandro; Ines Demmler, Monica (Malaysian Journal of Science, 1996)
This study reports the important characteristics of the South China Sea numerical model. A new algorithm is implemented as the original model has closed, open and periodic boundary conditions